A participação do estado na empresa em recuperação judicial - Moreira Neto, Rubem Aloysio Monteiro (2024)
This dissertation seeks to implement, in exceptional cases and situations, where there is relevant public interest, a normative mix, through the combination of existing rules in the national legal system, via “dialogue of sources” based on the classic conception of the German Professor Erik Jayme, between article 50, item X, of Law no. 11.101/2005 (creditors' company) with the provisions set out in the Brazilian Technological Framework, law no. 13,243/2016, with emphasis on the content of the fifth article of that regulation, opportunely consolidated under Brazilian law as a result of the promulgation of Constitutional Amendment no. 85 of 2015, which implemented a new legislative framework for the area of science, innovation and technological entrepreneurship (initially regulated by ordinary law no. 10,973/2004); the work intends to provide a path to emblematic cases where any Transnational Economic Group, as a public service provider (via concession or permission) can, with the consent of the Federation Entities and other creditors, opt for the alternative solution of overcoming the restrictions set in Law 12,767/2012 (in particular the content of article 18 – which makes it impossible to request judicial recovery for concessionary and permissioned companies) via the creditors' society. The methodological approach undertaken was treated under the equation of the triple helix, a theory developed in the United States by Professor Henry Etzkowitz, whose essence is a process of continuous development for the advancement of society through concrete actions in the economy. The implementation of this model requires a federal government policy, allowing the necessary metrics and adjustments to be processed and fixed as suggested in this academic work; given the essential and vital need for interaction (and complete harmony) between the 3 (three) pillars in the model adapted for our work (government/creditors/recovery court).